Uji Prestasi dan Emisi Diesel Berbahan Bakar Minyak Nabati Murni Untuk Pembangkitan Daya Di Daerah Terpencil - Roswati Nurhasanah; Arisma Chairulah (Sekolah Tinggi Teknik - PLN, 2020)
Pure Plant Oil (PPO) such as Pure Coconut Oil (PCO) and Pure Palm Oil (PPaO) could be a solution for electricity problem in remote areas in Indonesia. PCO and PPaO can be used as a fuel for diesel engine to produce electricity. This paper will compare and analyze the performance and emissions of the diesel power plant fueled with diesel fuel, PCO, and PPaO. For performance parameter, brake specific fuel consumption and thermal efficiency of diesel engine by using PPaO and PCO are higher than the diesel fuel, but the brake specific energy consumption are lower than the diesel fuel. That means diesel engine will be more efficient and have lower operational cost by using PPaO and PCO. For the emission parameters, CO2, CO, and CH emissions from PPaO and PCO are higher compared to diesel fuel. That means PPO have higher carbon emission than just using conventional diesel fuel. But, there are highly significant difference of less NOX emissions by using PCO and PPaO compared to the diesel fuel. That means it will be better using PPO because diesel engine has lack of high NOX emissions. These differences of diesel engine performance and emissions by PPaO, PCO, and diesel fuel are caused by the fuel characteristic differences such as cetane number, calorific value, and viscosity.